A Conversational Analysis of Grice’s Maxims Theories on Cooperative Principles at Undergraduate English Students - Hidayati Hidayati; Lukman Lukman (Linguistics and ELT Journal, 2018)
This study was aimed to analyze students’ conversation based on Grice’s maxim theory at the English department of  Muhammadiyah University of Mataram. The method of this research was qualitative. The result of this research showed that students were followed the maxim of quantity is 60 utterances, followed the maxim of quality is 16 utterances, followed the maxim of relevant is 24 utterances, and followed the maxim of manner is 6 utterances. Violated maxim of quantity is 47 utterances, violated maxim of quality is 27 utterances, violated maxim of relevant is 50 utterances and violated manner is 89 utterances. Violated maxims often happen than followed the maxims, total of violated whole the maxims are 213 and total of followed whole the maxims are 106 because the speaker and participants are come from different cultures, using informal language and their purpose in communication to maintain their social harmony.